Literature review: Evaluation of the Kurikulum Merdeka using the CIPP model - Muhamad Kosim Gifari; Zainal Arifin (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
Indonesia's participation in the Programme for International Students Assessment (PISA) showed unsatisfactory results, with reading, math, and science proficiency ranked in the bottom 10 out of 79 participating countries. This problem encourages academics in Indonesia to find solutions to improve the quality of education. The government developed the Kurikulum 2013 into the Kurikulum Merdeka to adapt to global developments. The Kurikulum Merdeka is expected to develop students' potential and abilities through critical, quality, expressive, applicative, varied, and progressive learning. Curriculum evaluation is needed to determine the value and meaning of the Kurikulum Merdeka implemented nationally. This study uses the literature review method to evaluate the Kurikulum Merdeka using the Context, Input, Process, and Product (CIPP) model. The results of the evaluation show that the Kurikulum Merdeka has achieved several levels of success in meeting the needs of students, teachers, and the community. The main findings include success in the internship program for vocational school students, Project-Based Learning at Madrasah Ibtidaiyah Yogyakarta, and early childhood art learning. However, challenges such as the availability of resources and facilities, the need to develop evaluation instruments, and educational staff training need to be addressed for future improvement. These evaluations provide recommendations such as increased cooperation between educational institutions and industry and increased training for educational staff. AbstrakPartisipasi Indonesia dalam Programme for International Students Assessment (PISA) menunjukkan hasil yang kurang memuaskan, dengan peringkat kemampuan membaca, matematika, dan sains berada di 10 terbawah dari 79 negara peserta. Masalah ini mendorong akademisi di Indonesia untuk mencari solusi guna meningkatkan kualitas pendidikan. Untuk menyesuaikan dengan perkembangan global, pemerintah mengembangkan Kurikulum 2013 menjadi Kurikulum Merdeka. Kurikulum Merdeka diharapkan dapat mengembangkan potensi dan kemampuan siswa melalui pembelajaran yang kritis, berkualitas, ekspresif, aplikatif, variatif, dan progresif. Evaluasi kurikulum diperlukan untuk memperoleh informasi dari nilai dan arti kurikulum merdeka yang telah diimplementasikan secara nasional. Penelitian ini menggunakan metode literature review untuk mengkaji evaluasi Kurikulum Merdeka menggunakan model Context, Input, Process, dan Product (CIPP). Hasil evaluasi menunjukkan bahwa Kurikulum Merdeka telah mencapai beberapa tingkat kesuksesan dalam memenuhi kebutuhan siswa, guru, dan masyarakat. Temuan utama mencakup keberhasilan dalam program magang siswa SMK, pembelajaran berbasis Project Based Learning di Madrasah Ibtidaiyah Yogyakarta, dan pembelajaran seni anak usia dini. Namun, tantangan seperti ketersediaan sumber daya dan fasilitas, serta perlunya pengembangan instrumen evaluasi dan pelatihan staf pendidikan, perlu diatasi untuk perbaikan di masa depan. Evaluasi ini memberikan rekomendasi seperti peningkatan kerjasama antara institusi pendidikan dan industri, serta peningkatan pelatihan untuk staf pendidikan.Kata Kunci: evaluasi kurikulum; kurikulum Merdeka; model CIPP